The life history of human foraging: Cross-cultural and individual variation - Koster, J.; Mcelreath, R.; Hill, K.; Yu, D.; Shepard JR, G.; Vliet, N. van; Gurven, M.; Kaplan, H.; Trumble, B.; Bird, R.B.; Bird, D.; Codding, B.; et al. (American Association for the Advancement of Science, 2020)
Hunters exhibit high skill across the life span, individuals vary substantially in skill, and age-related peaks vary across sites.